Discharge properties of single neurons in the dorsal nucleus of the lateral lemniscus of the rat - Bajo, V; Villa, A; de Ribaupierre, F; Rouiller, E (Elsevier, 1999)
The aim of the present study was to characterize the discharge properties of single neurons in the dorsal nucleus of the lateral lemniscus (DNLL) of the rat. In the absence of acoustic stimulation, two types of spontaneous discharge patterns were observed: units tended to fire in a bursting or in a nonbursting mode. The distribution of units in the DNLL based on spontaneous firing rate followed a rostrocaudal gradient: units with high spontaneous rates were most commonly located in the rostral part of the DNLL, whereas in the caudal part units had lower spontaneous discharge rates. The most common response pattern of DNLL units to 200 ms binaural noise bursts contained a prominent onset response followed by a lower but steady-state response and an inhibitory response in the early-off period. Thresholds of response to noise bursts were on average higher for DNLL units than for units recorded in the inferior colliculus under the same experimental conditions. The DNLL units were arranged according to a mediolateral sensitivity gradient with the lowest threshold units in the most lateral part of the nucleus. In the rat, as in other mammals, the most common DNLL binaural input type was an excitatory response to contralateral ear stimulation and inhibitory response to ipsilateral ear stimulation (EI type). Pure tone bursts were in general a more effective stimulus compared to noise bursts. Best frequency (BF) was established for 97 DNLL units and plotted according to their spatial location. The DNLL exhibits a loose tonotopic organization, where there is a concentric pattern with high BF units located in the most dorsal and ventral parts of the DNLL and lower BF units in the middle part of the nucleus.